IDEAL RECONSTRUCTION OF COMPENSATION AND REHABILITATION IN FALSE ARRESTS CASES - Nino Gilang Darmawan (Bhayangkara Law Review, 2024)
Basically, the problem of wrongful arrest cases is still quite common, where in practice, law enforcement officers sometimes use violence, coercion or pressure on a suspect during the investigation process. The actions of Law Enforcement Officials can be categorized as unlawful acts. The problem in practice is that the concepts of restitution (compensation) and rehabilitation, especially in cases of wrongful arrest, are still very rarely applied in the field of criminal law. The research method used in this research is a normative juridical research method. The materials studied are primary, secondary and tertiary legal materials. The research results show that basically requests for the right to compensation and rehabilitation can be submitted by the suspect, his family or his attorney. So heirs can also apply for rehabilitation. Likewise with compensation for losses. However, in practice and implementation, the concepts of restitution and rehabilitation, especially in cases of wrongful arrest, are still rarely applied in the field of criminal law. The problem of wrongful arrest, of course, not only needs to be corrected and is homework that needs to be addressed by the government, but also requires concrete solutions whose benefits and justice can be felt directly by the community, especially towards suspects or defendants and/or the families of suspects or defendants who are victims of wrongful arrest. . So in this research, researchers reconstruct an ideal and fair solution for all parties, including law enforcement officials who make mistakes in criminal procedures, as well as for suspects or defendants and/or the families of suspects or defendants who are victims of wrongful arrest.